Knowledge in palliative care of nursing professionals at a Spanish hospital - Elena Chover-Sierra; Antonio Martínez-Sabater; Yolanda Lapeña-Moñux (Universidade de São Paulo, 2017)
Resume Objective: to determine the level of knowledge in palliative care of nursing staff at a Spanish tertiary care hospital. Method: descriptive, cross-sectional study. Data were collected about the results of the Spanish version of the Palliative Care Quiz for Nurses (PCQN), sociodemographic aspects, education level and experience in the field of palliative care. Univariate and bivariate descriptive analysis was applied. Statistical significance was set at p < 0.05 in all cases. Results: 159 professionals participated (mean age 39.51 years ± 10.25, with 13.96 years ± 10.79 of professional experience) 54.7% possessed experience in palliative care and 64.2% educational background (mainly basic education). The mean percentage of hits on the quiz was 54%, with statistically significant differences in function of the participants' education and experience in palliative care. Conclusions: although the participants show sufficient knowledge on palliative care, they would benefit from a specific training program, in function of the mistaken concepts identified through the quiz, which showed to be a useful tool to diagnose professionals' educational needs in palliative care.